P233 Patient knowledge and opinions of their healthcare devices. (12th November 2019) - Rowe, C; Young, K; Singh, S; Suresh-Nair, A; Usmani, O
Abstract : Inhaled medications are the cornerstone of therapy for chronic obstructive pulmonary disease (COPD) patients, yet ∼1/3 of patients make critical errors when using their inhaler devices that can impact on therapeutic benefit. The UK Inhaler Group (UKIG), surveyed their member organisations and identified 5 themes of concern potentially affecting patients' use of inhalers: (1) patient training and knowledge of their inhalers, (2) inhalers in the acute emergency, (3) environmental issues, (4) spacer use and (5) inhalers in schools. The aims of this study were to assess patients' knowledge regarding use of their inhaler devices and gauge their opinions on inhalers in order to examine patient-relevant factors that influence use of their inhaled medication. COPD patients (n=138) were individually interviewed before their clinic appointment at a tertiary care centre. A 47-item questionnaire was devised to explore patients' knowledge and opinions related to their inhalers, and their understanding regarding inhaler themes (2 - 5). Patients' knowledge on inhaler use was found lacking in themes (1 - 4). Of concern, 55/138 (40%) of patients had not had their inhaler technique reviewed by a healthcare professional (HCP) in the last 12 months, demonstrating a clear risk of deterioration in inhaler technique. 90/138 (65%) of patients had not been shown how to use their inhaler for when they had breathing difficulty in an acute emergency. 24/138 (17%) of patients demonstrated knowledge of environmental issues specific to inhalers. In terms of spacer use, interestingly 74/121 (61%) of patients were unable to explain why a spacer was useful. Understanding the accessibility of inhalers in schools was difficult to gauge as these were COPD rather than asthma patients; however universally high ratings of importance were given to the presence of inhalers in schools. Patients' knowledge in inhaler use is inconsistent and lacking. Importantly, the lack of regular inhaler technique review by HCPs exposes a risk to patient health and contributes to the prevailing critical errors observed. Our data shows that deficiencies of patient knowledge in the main themes identified, particularly in the use of inhalers in an emergency, highlight significant concerns and the need for action to be taken.